Riset Pengembangan Ilmu Pengetahuan dan Teknologi (IPTEK) - Iwan Kuswanto (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
This research discusses road pavement repairs on expansive soil using various methods such as rigid pavement with additional pillars, the Chicken Claw system, and flexible pavement supported by lime columns or alternative material mixtures. One efficient technical solution is the use of industrial waste such as rice husk ash and carbide waste, which have the potential to be used as environmentally friendly soil improvement materials. The lime column technique has been proven to be able to reduce expansive soil pressure and flexible plate deformation in laboratory scale tests, with an optimal distance between columns of around three times the column diameter. Column modification by enlarging the base can reduce differential settlement and heaving, making it an alternative for sustainable flexible pavement structural repairs. This research roadmap is planned for three years with stages of 3D testing in the laboratory, field tests, and evaluation of road pavement structures. The final results of the research are expected to create a road pavement system that is not only technically effective but also supports the concept of environmentally friendly construction (green construction), with a target of full implementation in 2020.